(untitled) (Research, Society and Development, 2023)
The objective of this research was to describe vitamin D and discuss its physiology, in a systematic and exploratory way, reviewing data from the literature, and obtaining analysis in PubMed databases about the concentrations considered adequate. Vitamin D, in addition to having a nutritional role, has as its main function to regulate bone metabolism. Studies show that the lack of vitamin D in epidemic proportions causes several health problems, especially frequent falls in the elderly and the main benefits favored by it, the factors that contribute to its deficiency and the appropriate means of prevention in risk groups. In the elderly, vitamin D insufficiency is common, losing bone mass and having a large increase in falls and fractures. Falls cause morbidity and mortality in the elderly. The use of active vitamin D is necessary, as it improves physical capacity in the elderly, thus reducing the risk and incidence of falls.